2007
DOI: 10.1038/sj.clpt.6100015
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of CYP2D6*10 and *14 Alleles and their Influence on the Metabolic Activity of CYP2D6 in a Healthy Chinese Population

Abstract: To study the frequency of CYP2D6(*)10 and (*)14 alleles in a healthy Chinese population, and the influence of these two alleles on the metabolic activity of CYP2D6. CYP2D6(*)10 and (*)14 genotypes of 295 healthy Chinese subjects were determined using a tetra-primer method and allele-specific amplification. CYP2D6 phenotypes of 131 subjects were determined using dextramethorphan as probe drug. There were 10 subjects with a (*)14 allele, including one homozygous for (*)14. The gene frequency of (*)10 and (*)14 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 13 publications
5
24
1
Order By: Relevance
“…These allele frequencies are similar to those that have been reported in other Asian populations but higher than those reported for Caucasians and African Americans, in whom the frequency of the CYP2D6*10 allele was found to be 2%-5% [9,10] . In Japanese psychiatric patients, the number of CYP2D6*10 alleles has been found to significantly affect dose-corrected plasma risperidone levels [18] .…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…These allele frequencies are similar to those that have been reported in other Asian populations but higher than those reported for Caucasians and African Americans, in whom the frequency of the CYP2D6*10 allele was found to be 2%-5% [9,10] . In Japanese psychiatric patients, the number of CYP2D6*10 alleles has been found to significantly affect dose-corrected plasma risperidone levels [18] .…”
Section: Discussionsupporting
confidence: 70%
“…Additionally, CYP2D6 polymorphisms (*10, *5) affect the pharmacokinetic parameters of other atypical antipsychotic drugs, such as risperidone [8] and aripiprazole [9] . The allele frequencies of CYP2D6*10 (rs1065852, allele C>T) mutations are 48%-70% [10] and 30%-50% [11] in Chinese and other Asian populations (eg, Japanese and Korean populations), respectively. However, the effects of the CYP2D6*10 (rs1065852) mutation on the pharmacokinetics of iloperidone in clinical practice remain unknown.…”
Section: Original Articlementioning
confidence: 99%
“…It is an important enzyme responsible for the metabolism of 25% of drugs, including antipsychotics and antidepressants. It is polymorphically expressed, being absent in 6-10% of Caucasians and 1% of Asians, 1 who are known as poor metabolizers (PMs). Patients with two wild-type (wt) or functional alleles are referred to as extensive metabolizers (EMs).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a number of studies have found that around 7% of Caucasians are PMs compared with 1% of Asians, with data for other ethnic groups less cogent. 21 However, fewer Asians metabolise CYP2D6 normally, largely because of high frequencies of the *10 allele, 22 resulting in a 24 a Some studies make no distinction between EMs and IMs whereas others classify these as homozygous EMs and heterozygous EMs respectively (but not all heterozygous EMs will necessary be IMs). Similarly, not all studies make distinctions with ultrarapid metabolisers (and not all pharmacogenetic tests are capable of detecting patients with multiple copies of alleles and thus making this distinction).…”
Section: *41x2mentioning
confidence: 99%
“…This decreased activity allele, which is rare in Caucasian populations, has been estimated to be as high as 55% in Chinese populations. 21,23 The classification used in Table 3 is the one that is used by the first approved pharmacogenetic test, the AmpliChip. This test also tests for CYP2C19 and patients are given either an extensive metaboliser (EM) or a PM phenotype, reflecting the fact that the *1 allele is a normal activity allele whereas *2 and *3 are associated with loss of function.…”
Section: *41x2mentioning
confidence: 99%